The Concept of Defense Management in the 21st Century within Indonesia Maritime Security Framework - Herlina Juni Risma Saragih; Rayanda Barnas; Deffi Ayu Puspito Sari (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Conflict of Maritime Security in the Asia Pacific region, especially South China Sea is a conflict that has long occurred and a problem that is often raised both in a regional and international level. Related to the conflict takes Strategy and Management of the State's defense to anticipate the impact of the conflict situations on defense and security of the region. The purpose of this study is to analyze the concept of Defence Management Indonesia in the 21st century in the context of Indonesian Maritime Security, Case Studies U.S Rebalancing in Asia Pacific and South China Sea conflict, as well as to determine the readiness of Defence Management capabilities in the face of threats. The method used is a qualitative method of data collection methods through in-depth interview to the informant. The results showed that in order to improve maritime security in Indonesia has not been implemented in a structured and comprehensive defense in accordance with the management perspective of the countries more advanced, especially on defense preparedness in logistics management as a managing and defense equipment avaible owned by Indonesia government. Based on these results it is suggested the need for socialization implementation of Defense Management in Asia Pacific by Indonesia government in the context of Maritime Security comprehensively.